Leadership Stability in Army Reserve Component Units - Lippiatt, Thomas F. (RAND Corporation, 2013)
This monograph reports results of a study to determine the level and causes of personnel turbulence among Army Reserve Component unit leadership and the effects this turbulence can have on training and preparation for future missions, as well as possible policy and practice options that could mitigate those effects.